Energy efficient rehabilitation of a historic building in Tucson, Arizona: investigating the potential for energy conservation while preserving the building’s historical integrity - Alhazzaa, Kifah (Journal of Architecture and Urbanism, 2023)
The focus of this study was to investigate the feasibility of transforming historically significant buildings with high energy requirements into high-performance constructions. The researcher suggested adaptive reuse for the case study, recommending that the building be converted from a warehouse into a café and art studio, which would be in line with the surrounding art district in Tucson, Arizona. As a result of the change in design, everything from the floor plans to the building facades and the mechanical systems were modified. During the visit to the location, the researcher was able to identify the primary factors that led to the low energy efficiency. The study was conducted using the real-life energy simulation that the DOE-2 simulation engine provides. During the process of redesigning the building, the researcher utilized both passive and active design strategies to evaluate how these techniques impacted the amount of energy consumed by the structure. The total amount of energy that was saved from all of the implemented solutions was compared to the total amount of energy that was consumed by the base case (the existing condition). The findings indicated that the chosen case study had a significant potential for reducing energy consumption, with savings amounting to more than 50 percent of the total energy usages.